Investigating international strategic brand management and export performance outcomes in the B2B context. Issue 1 (18th December 2019) - Pyper, Keith; Doherty, Anne Marie; Gounaris, Spiros; Wilson, Alan
Abstract : Purpose: Drawing on Resource-based Theory, the purpose of this paper is to empirically examine the effect of International Strategic Brand Management (SBM) on export performance within the Business-to-Business (B2B) context. To be able to purposely assess the relationship, this paper also sets out to discover what antecedent international resources, (financial resources) and international capabilities (market information, branding and marketing planning) contribute to the ability of B2B exporters to effectively manage their brands abroad. Design/methodology/approach: A mixed method firm-level approach was employed. First, a qualitative study of 34 in-depth interviews explored the focal inter-relationships and constructs identified within the literature. A survey of 208 successful UK exporters was then conducted and the results were analysed using structured equation modelling. Findings: The results confirm that certain marketing capabilities (branding and marketing planning) are advantageous antecedents to the employment of effective SBM in foreign markets which, in turn, leads to increased financial and market performance internationally. Practical implications: This paper outlines practical brand management considerations managers need to account for to achieve effective exporting. Practitioners are advised to prioritise the development of robust international branding and marketing planning capabilities which can enable them to exploit their limited financial resources for optimal benefits. Furthermore, by developing these capabilities, firms can focus on the essence of their brand and communicate their brand image through the effective strategic management of their brand to business customers, evoking positive brand associations, enhanced perceived brand value and the achievement of increased export performance. Originality/value: This paper is the first to focus on international SBM as the deterministic factor leading to improved B2B export performance. An innovative framework is offered which positions the pivotal role of International SBM as the central focus. The construct for international branding capabilities is extended specifically for use in the B2B domain.